Das Hin und Her der Blicke, Eidola in der Pupille Augenförmiger Gemmen: Liebesgeschenke mit Amulettcharakter? - Weiss, Carina (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
The presented group of late Republican to early Imperial intagli consists of round layered stones (sardonyx, cornelian onyx) with a flat reverse side, which are strongly convex on the front side. Their horizontally stacked and differently coloured plies are sanded on the front to form concentric rings around a dark centre. The motif incised in this centre looks like an eidolon in the pupil of a ’fisheye’. Most of these motifs can be interpreted against the background of Augustan love poetry. It is possible that gems of this kind were gifts of love and, due to their striking design as an eye, also had an apotropaic function.